Les résultats du modèle intersectoriel du Québec — les postes traditionnels de la comptabilité nationale et les multiplicateurs de revenus - Truchon, Michel (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
The author shows how, under certain conditions, results from the Quebec Input-Output model can be aggregated to obtain familiar components of the National Accounts and to derive income multipliers. These multipliers are also discussed and compared to other types of multipliers.